An optimized abnormal muscle response recording method for intraoperative monitoring of hemifacial spasm and its long-term prognostic value. (February 2017) - Huang, Chuyi; Miao, Suhua; Chu, Heling; Dai, Chuanfu; Wu, Jinting; Wang, Junhua; Zuo, Huancong; Ma, Yu
Abstract: Background: Intraoperative electrophysiological monitoring is used to determine whether decompression is sufficient during microvascular decompression (MVD) for hemifacial spasm (HFS). However, the real offending vessel is sometimes neglected by the neurosurgeons. Here, we reported our experience in using optimized abnormal muscle response (AMR) monitoring and continuous intraoperative monitoring for MVD. Methods: This study included 2161 HFS patients who underwent MVD using traditional (1023 patients) and optimized (1138 patients) methods. Modified AMR monitoring was adopted in our study, with the zygomatic branch of the facial nerve stimulated and the temporal branch, buccal branch, marginal mandibular branch and cervical branch of the facial nerve detected for AMR. These cases were analyzed retrospectively with emphasis on the postoperative outcomes and intraoperative findings. The therapeutic effect was evaluated at day 1, month 3 and year 1 after operation. Results: The relief rate at day 1, month 3 and year 1 after operation for patients who employed optimized AMR recording method was 95.1%, 97.4% and 99.3%, comparing with 92.2%, 95.0% and 97.8% in traditional method. There was significant difference in achieved immediate remission and recovery rate during 12-month follow-up between the two groups (P < 0.05). The modified intraoperative monitoring showed the sensitivity of AMR disappearance to judge the relief at day 1, month 3 and year 1 after HFS operation was 95.7%, 96.3% and 97.3%, respectively; the specificity was 44.6%, 43.3% and 50.0%, respectively; the accuracy was 93.1%, 94.9% and 97.4%, respectively. Conclusions: Our findings demonstrated that the optimized method could improve the positive detection rate of AMR and accuracy of decompression effect prediction. The evaluation for the decompression effect by optimized intraoperative monitoring can increase the immediate remission rate and reduce the delayed recovery rate. Highlights: Providing an optimized AMR recording method during MVD for HFS. Optimized method improves the positive detection rate of AMR. Optimized method increases accuracy of decompression effect prediction. Increasing the immediate remission rate and reducing the delayed recovery rate.